Arabidopsis det2 Is Defective in the Conversion of (24R)-24-Methylcholest-4-En-3-One to (24R)-24-Methyl-5α-Cholestan-3-One in Brassinosteroid Biosynthesis - Noguchi, Takahiro (American Society of Plant Physiologists, 1999)
Previously, we have shown that the Arabidopsis det2 (deetiolated2) mutant is defective in the biosynthesis of brassinosteroids (BR) and that DET2 (a steroid 5α-reductase) acts early in the proposed BR biosynthetic pathway. In this paper we present further biochemical characterization of det2. We have undertaken metabolic experiments with (2)H-labeled substrates of intermediates involved in the formation of campestanol from campesterol, and quantitative analysis of intermediates in Arabidopsis wild type and det2. The results of these studies indicate the early operating steps of BR biosynthesis as: campesterol → 4-en-3β-ol → 4-en-3-one → 3-one → campestanol in Arabidopsis, with det2 deficient in the conversion of 4-en-3-one to 3-one. We have also detected these intermediates in the formation of campestanol from campesterol and their metabolic conversions using cultured cells of Catharanthus roseus. These studies confirmed the biosynthetic sequence of events from campesterol to campestanol as was found in Arabidopsis. As such, the originally proposed biosynthetic pathway should be modified.